IMPROVING STUDENTS' READING COMPREHENSION ABILITY ON RECOUNT TEXT BY USING QUESTION-ANSWER RELATIONSHIP (QAR) STRATEGY - Icha Novita Sari; Nurhasanah Nurhasanah; Trisilia Devana (JOLE (Journal of Language Education), 2023)
This research aims to determine whether a Question-Answer Relationship (QAR) strategy can improve students` reading comprehension ability in recounting text in the second grade of SMP Negeri 21 OKU. The research method was a pre-experimental design, one-group pre-test, and post-test. This means that the researcher only focused on one class as an experimental class and did not use a control class. The population of this research was students in the second grade of the SMP N 21 OKU. The sample in research class VIII A consisted of 27 students. Simple random sampling was used. The instruments used to conduct the data were the pretest and posttest. The data were analyzed by scoring students' correct answers, percentage student scores, means, and statistical analysis using a paired sample t-test. The results of this study indicate that the QAR strategy is effective in improving students` reading comprehension. The scoring average of the pre-test was 54,63 and the scoring average of the post-test was 67,41. This indicated that there were significant differences before and after treatment. The data analysis also showed that the significance value (2-tailed) is 0,000 which is less than the significance level of 0,05 (5%). This means that the Alternative Hypothesis (H1) is accepted and the Null Hypothesis (H0) is rejected. This shows that the QAR strategy is effective in teaching reading.